Avasimibe Alleviates Disruption of the Airway Epithelial Barrier by Suppressing the Wnt/β-Catenin Signaling Pathway - Zhou, Zicong; Liang, Shixiu; Zhou, Zili; Liu, Jieyi; Meng, Xiaojing; Zou, Fei; Yu, Changhui; Cai, Shaoxi (Frontiers in Pharmacology, 2022)
Avasimibe (Ava) is an acetyl-CoA acetyltransferase 1(ACAT1) specific inhibitor and an established medicine for atherosclerosis, owing to its excellent and safe anti-inflammation effects in humans. However, its efficacy in asthma have not yet been reported. We first administrated varying concentrations of Avasimibe to House Dust Mites (HDM)-induced asthmatic mice, results showed that 20 mg/kg Avasimibe most significant reduced IL-4 and IL-5 production in Bronchoalveolar Lavage Fluid (BALF) and total IgE in serum, the Avasimibe treatment also exhibited lower mucus secretion, decreased goblet and basal cells but increased ciliated cells compared to HDM group. And the redistribution of adherens junctions (AJs) proteins induced by HDM was far more less upon Avasimibe administration. However, Avasimibe did not reduce cholesterol ester ratio in lung tissues or intracellular, which is Avasimibe mainly effects. Further analysis confirmed that Avasimibe impaired epithelial basal cells proliferation independent on regulating cholesterol metabolism and we analyzed datasets from GENE EXPRESSION OMNIBUS (GEO) database, then found that KRT5 gene (basal cell marker) expression is correlated with β-catenin gene. Moreover, we found that β-catenin localized in cytomembrane upon Avasimibe treatment. Avasimibe also reduced β-catenin phosphorylation in cytoplasm and inactivated the Wnt/β-catenin signaling pathway induced by HDM, thereby alleviating the airway epithelial barrier disruption. Taken together, these findings indicated that Avasimibe has potential as a new therapeutic option for allergic asthma.